Bernoulli Differential Equations Solution Using Adomian Decomposition Method by Matlab - Safaa Abu-Amr; Tebra Almajbri; Amina Mohammed (AlQalam Journal of Medical and Applied Sciences, 2024)
This paper uses the Adomoian decomposition method to solve Bernoulli differential equations, a type of nonlinear differential equation with numerous physical applications. The test problems included numerous Bernoulli differential equations with varied nonlinear component exponents, which were described using a decomposition-based numerical approach. The results are equally accurate in tables and graphs as the classical method. تستخدم هذه الورقة طريقة التحلل الأدوموي لحل معادلات برنولي التفاضلية، وهو نوع من المعادلات التفاضلية غير الخطية ذات التطبيقات الفيزيائية العديدة. تضمنت مشاكل الاختبار العديد من معادلات برنولي التفاضلية ذات الأسس المكونة غير الخطية المتنوعة، والتي تم وصفها باستخدام نهج عددي قائم على التحلل. النتائج دقيقة بنفس القدر في الجداول والرسوم البيانية مثل الطريقة الكلاسيكية